Introduction to ethnographic research a guide for anthropology - Kirner, Kimberly; Mills, Jan (SAGE, 2020)
"Introduction to Ethnographic Research streamlines learning the process of research, speaks to the student at a foundational level, and helps the reader conquer the apprehensions of mastering research methods. Written in a conversational style, authors Kimberly Kirner and Jan Mills use a focus on scaffolding across the chapters to help the student transition from step to step in the research process. Case studies and first-hand accounts are also featured in each chapter, allowing the student to see the early steps, successes and at times failures that accomplished researchers experienced in their past. These real examples further encourage the student that even the best researchers failed along the way, and more importantly, learned from those mistakes. This text is designed to be used as a stand alone book, but is enhanced by the use with the supplemental workbook, Doing Ethnographic Research by the same authors. This text has call-outs to the supplemental text, which allow for application and practice of the material learned."--Provided by publisher.